Research Letter: PTSD Symptom Severity and Multiple Traumatic Brain Injuries Are Associated With Elevated Memory Complaints in Veterans With Histories of Mild TBI. Issue 6 (22nd November 2021) - Sorg, Scott F.; Werhane, Madeleine L.; Merritt, Victoria C.; Clark, Alexandra L.; Holiday, Kelsey A.; Hanson, Karen L.; Jak, Amy J.; Schiehser, Dawn M.; Delano-Wood, Lisa
Abstract : Objective: The evaluation of memory complaints in mild traumatic brain injury (mTBI) remains an important clinical consideration, especially in the context of comorbid psychiatric symptoms such as posttraumatic stress disorder (PTSD). We compared subjective memory complaints in veterans with and without a history of mTBI, examined ratings between those with single versus multiple mTBIs, and investigated associations between memory complaints and PTSD symptom severity. Methods: 117 outpatient veterans (mTBI: n = 79 [single mTBI: n = 22, multiple mTBI: n = 57], military controls [MCs]: n = 38) completed a TBI history assessment, the Prospective-Retrospective Memory Questionnaire (PRMQ), and the PTSD Checklist–Military Version (PCL-M). Results: Hierarchical multiple regression showed that greater PCL-M scores significantly predicted elevated PRMQ-Total scores, accounting for 38% of the variance explained ( P < .001). mTBI status predicted an additional 5% of variance in memory complaints ( P < .01). The multiple-mTBI group endorsed more memory complaints than either MCs ( P < .01) or the single-mTBI group ( P < .05), who did not differ from MCs ( P > .50). Conclusions: Comorbid PTSD symptoms are an important factor when considering memory complaints in veterans with a reported history of mTBI. However, independent of comorbid PTSD symptoms, mTBI status—particularly in the context of repetitive neurotrauma—uniquely contributes to memory complaints. Findings suggest that veterans with a history of multiple mTBIs may be a particularly vulnerable group in need of specialized interventions and/or psychoeducation.